2015
DOI: 10.1186/s12887-015-0379-7
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition promotion approaches preferred by Australian adolescents attending schools in disadvantaged neighbourhoods: a qualitative study

Abstract: BackgroundLinks between socioeconomic disadvantage and unhealthy eating behaviours among adolescents are well established. Little is known about strategies that might support healthy eating among this target group. This study aimed to identify potential strategies and preferred dissemination methods that could be employed in nutrition promotion initiatives focussed on improving eating behaviours among socioeconomically disadvantaged adolescents.MethodsSemi-structured interviews were conducted in 2011 among 22 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 64 publications
5
37
0
Order By: Relevance
“…Indeed, empirical evidence from both developed [ 33 , 34 ] and developing economies including India [ 13 , 35 , 36 ] suggests that the palatability of energy-dense, nutrient-poor foods over nutritious foods is highly appealing and this leads to its excessive consumption among adolescents. Since, such excessive consumption of nutrient-poor foods can result in overweight and obesity [ 4 , 6 ], Indian schools should supply palatable nutritious foods to students, as recommended in the past [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, empirical evidence from both developed [ 33 , 34 ] and developing economies including India [ 13 , 35 , 36 ] suggests that the palatability of energy-dense, nutrient-poor foods over nutritious foods is highly appealing and this leads to its excessive consumption among adolescents. Since, such excessive consumption of nutrient-poor foods can result in overweight and obesity [ 4 , 6 ], Indian schools should supply palatable nutritious foods to students, as recommended in the past [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the respondents proposed that schools should supply tasty nutritious foods at economical prices. Studies of Nordic [ 58 ] and Australian adolescents [ 59 ] have also suggested that increased accessibility of tasty nutritious meals and snacks at a low cost could help them to make healthier food choices. Taste is an important determinant of food choice [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, home economics is compulsory only in Year 7 or 8 in Australian high schools which is not enough for developing sustainable food skills such as food preparation. Australian adolescents have been reported as recognising the importance of developing food preparation skills through home economics and indicated that high school curriculum should provide them with this opportunity (Stephens et al, 2015). A study by Tysoe and Wilson (2010) concluded that nutrition education and positive food environment may support healthy dietary behaviours of adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Mostly, food that was sold in school canteens was defined as unhealthy, expensive and contradicting what is being taught in food literacy classes. Australian adolescents have suggested that the elimination of unhealthy foods from school canteens and increased accessibility of nutritious meals and snacks at a low cost could help them to make healthier food choices (Stephens et al, 2015). There is often a battle between healthy and unhealthy foods within the school setting (Mikkelsen, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation